Embedding an Education Intervention about Shared Decision Making into an RCT: Ensuring competency and fidelity - Amy B. Zelenski; Karlie Haug; Kyle J. Bushaw; Anne Buffington; Taylor Bradley; Kristine L. Kwekkeboom; Lily Stalter; Bret M. Hanlon; Maureen J. Wakeen; Roy A. Jhagroo; Laura J. Maursetter; Sara K. Johnson; et al. (Elsevier, 2024)
Objective: To describe the outcomes of training nephrology clinicians and clinical research participants, to use the Best Case/Worst Case Communication intervention, for discussions about dialysis initiation for patients with life-limiting illness, during a randomized clinical trial to ensure competency, fidelity to the intervention, and adherence to study protocols and the intervention throughout the trial. Methods: We enrolled 68 nephrologists at ten study sites and randomized them to receive training or wait-list control. We collected copies of completed graphic aids (component of the intervention), used with study-enrolled patients, to measure fidelity and adherence. Results: We trained 34 of 36 nephrologists to competence and 27 completed the entire program. We received 60 graphic aids for study-enrolled patients for a 73% return rate in the intervention arm. The intervention fidelity score for the graphic aid reflected completion of all elements throughout the study. Conclusion: We successfully taught the Best Case/Worst Case Communication intervention to clinicians as research participants within a randomized clinical trial. Innovation: Decisions about dialysis are an opportunity to discuss prognosis and uncertainty in relation to consideration of prolonged life supporting therapy. Our study reveals a strategy to evaluate adherence to a communication intervention in real time during a clinical study.